Prinsip-Prinsip Pengembangan Kurikulum Pendidikan Agama Islam - Sindi Pramita; Saifundi; Siti Halimah; Muhammad Ridha (ASSUNNAH PRESS, 2025)
Changes in government policies in the field of education, including the continuous development of the national curriculum, require adjustments to the PAI curriculum to remain relevant and in line with national education policies. Each student has different needs in understanding and practicing the teachings of Islam. Each learner has different needs in understanding and practicing the teachings of Islam. Therefore, the PAI curriculum needs to be designed in such a way as to meet the needs and characteristics of diverse learners. This research uses the library research method, an approach to existing literature. There are several principles in the development of PAI curriculum, namely the principle of relevance, the principle of flexibility, the principle of continuity, the principle of efficiency, and the principle of effectiveness The curriculum can be changed and modified dynamically to keep up with the times without ignoring the noble values of society. This process of change and modification is referred to as curriculum development.